(untitled) (Medical Forum Monthly, 2023)
Objective: Acute kidney injury (AKI) is associated with increased mortality in the intensive care unit (ICU). Fluid therapy is the mainstay of treatment for AKI. A positive fluid balance has been known to worse AKI and lead to poor long term outcome. We evaluate the role of positive fluid balance and its effect on renal outcome in our setup Study Design: Retrospective study Place and Duration of Study: This study was conducted at the Intensive Care Unit of Dr. Ziauddin Hospital Clifton Campus. from January 2021 to December 2021 Materials and Methods: A retrospective study done in patients requiring ICU admission. Patients were excluded for post renal AKI, Stage 5 chronic kidney disease, renal transplant or renal failure on admission day. AKI was defined as per the Kidney Disease Improving Global Outcome creatinine based criteria. Results: 302 patients were included in the study. Mean age was 64.49±15.92. At the time of admission SOFA score was 4.03±3.82. 274 patients were in positive fluid balance of 5 liters. Among these patients stage 1 AKI was present in 234, stage II in 9 and stage III in 28. Similar trend was observed in negative fluid balance group (p<0.59). In positive fluid balance group 62% patients were discharged from hospital while mortality was observed in 37.95% (p <0.89). Conclusion: The results suggest that the impact of positive fluid balance on AKI was non inferior to negative fluid balance in critically ill patients.